The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00007890-200204270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Brain death does not affect hepatic allograft function and survival after orthotopic transplantation in a canine model1, 2

Abstract: In contrast to previous reports in rodent models, our study shows that brain death does not cause significant liver dysfunction in the donor before organ removal. Donor brain death and prolonged liver graft preservation do not interact significantly to impair liver function and survival after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
1
18
0
2
Order By: Relevance
“…2003'te yap tık la rı ça lış mada, be yin ölü mü ta nı sı ko nul du ğu an da ki ve 16 saat son ra ki se rum AST, ALT, LDH ve to tal bi li ru bin de ğer le ri ara sın da an lam lı fark bu lun ma dı ğı nı gös-ter miş ler dir. 8 Ça lış ma mız da, ya tış gü nü ve be yin ölü mü ta nı sı nın kon du ğu gün de ki la bo ra tu var veri le ri in ce le di ğin de; AST, ALT de ğer le ri nin ya tış gü nü da ha yük sek, to tal bi li ru bin de ğe ri nin ise ben zer ol du ğu gö rül mek le be ra ber, iki gün ara sın -da an lam lı fark lı lık bu lun ma mış tır.…”
Section: Tar Tiş Maunclassified
“…2003'te yap tık la rı ça lış mada, be yin ölü mü ta nı sı ko nul du ğu an da ki ve 16 saat son ra ki se rum AST, ALT, LDH ve to tal bi li ru bin de ğer le ri ara sın da an lam lı fark bu lun ma dı ğı nı gös-ter miş ler dir. 8 Ça lış ma mız da, ya tış gü nü ve be yin ölü mü ta nı sı nın kon du ğu gün de ki la bo ra tu var veri le ri in ce le di ğin de; AST, ALT de ğer le ri nin ya tış gü nü da ha yük sek, to tal bi li ru bin de ğe ri nin ise ben zer ol du ğu gö rül mek le be ra ber, iki gün ara sın -da an lam lı fark lı lık bu lun ma mış tır.…”
Section: Tar Tiş Maunclassified
“…Clinical and experimental studies have shown that BD in the donors has a significant impact on the graft quality (21). This result is supported as the livers from a living donor have superior post-transplant survival rate compared with those from BD donors (22,23).…”
Section: Discussionmentioning
confidence: 86%
“…This report was similar to their report published in 2001, which found no clear reason for the increase, but implied the damage to the hepatocytes as a potential candidate. The study by Compagnon et al [35], published in 2002, observed that there are no significant changes in AST, ALT, LDH, gamma-glutamyl transpeptidase (GGT), and total bilirubin (except for alkaline phosphatase (AKP)) before organ removal in brain-dead donors compared with those that have been brain dead for 16 h. After orthotopic transplantation of donor livers cold-preserved for 24 h in the University of Wisconsin solution, there were no significant differences in AST, ALT, and LDH in two groups, which gradually became normal after 2-3 days. Golling et al [36] reported in 2003 that aspartate aminotransferase/glutamate-oxaloacetate transaminase (AST/GOT) of hypotensive and normotensive brain-dead pigs both increased after induction of brain death.…”
Section: Changes In Liver Functionsmentioning
confidence: 98%
“…The decrease in organ function is associated with donor organ inflammation induced by the release of cytokines and chemokines before procurement of brain-dead organs [13]. Compagnon et al [35] showed that the effects of brain death on liver graft are hard to ascertain. Most research has been established based on rodent brain-dead models.…”
Section: The Influence Of Brain Death On the Outcomes Of Transplantationmentioning
confidence: 99%